Pharmacist Provided Spirometry Services: A Scoping Review - Valentino AS; Eddy E; Woods Z; Wilken L (Dove Medical Press, 2021)
Alexa Sevin Valentino,1 Emily Eddy,2 Zachary Woods,3 Lori Wilken4 1Pharmacy Practice and Science, The Ohio State University College of Pharmacy, Columbus, OH, USA; 2Pharmacy Practice, Ohio Northern University, Ada, OH, USA; 3Pharmacy Education and Innovation, The Ohio State University College of Pharmacy, Columbus, OH, USA; 4Pharmacy Practice, University of Illinois at Chicago College of Pharmacy, Chicago, IL, USACorrespondence: Alexa Sevin ValentinoPharmacy Practice and Science, The Ohio State University College of Pharmacy, 500 W 12th Ave, 129B Parks Hall, Columbus, OH, 43210, USATel +1 614 292 1186Email valentino.49@osu.eduPurpose: Despite international guidelines' recommendations, spirometry is underutilized in the diagnosis and management of asthma and COPD. Spirometry may be an opportunity for trained pharmacists to meet the needs of patients with suspected or diagnosed lung conditions. The aim of this scoping review is to describe the literature including pharmacist provided spirometry services, specifically to identify: 1) the models of pharmacist provided spirometry services, and additional services commonly offered alongside spirometry, 2) pharmacist training and capability to obtain quality results, and (3) pharmacist, physician, and patient perspectives.Methods: In September 2020, a comprehensive literature search in PubMed and EMBASE was conducted to identify all relevant literature on the topic of pharmacist provided spirometry services using the search term: "pharmacist or pharmacy" and "spirometry or pulmonary function test or lung function test." Literature was screened using inclusion/exclusion criteria and selected articles were charted and analyzed using the themes above.Results: A total of 27 records were included. The scoping review found that pharmacist provided spirometry has been conducted around the world in community pharmacies and clinic settings. Community pharmacists may increase access to spirometry screening; the lack of communication with primary care providers and remuneration are barriers that need to be overcome to optimize the utility of the service. Clinic-based services are interprofessional and collaborative, allowing a patient to receive the test, results, diagnosis, and medication changes in one visit. Following comprehensive training, pharmacists felt confident in their ability to perform spirometry and met quality standards at acceptable rates.Conclusion: Spirometry is an opportunity for pharmacists to improve evidence-based practice for screening and diagnosing lung conditions along with providing comprehensive services to complement testing. Data around provider and patient perspectives is limited and should be further investigated to determine if providers and patients would value and collaborate with pharmacists providing spirometry services.Keywords: pulmonary function test, community pharmacy, clinical pharmacy services, asthma, chronic obstructive pulmonary disease, COPD, lung disease